Properties of friction during the impact between tennis racket surface and ball - Maeda, H; Okauchi, M. (Procedia Engineering, 2010)
The "feel" of hitting a ball with a tennis racket has been quantified by vibrations to the hand and by the coefficient of restitution. As play styles are shifting toward hitting with topspin to the ball, the friction between the ball and racket surface, in other words tangential forces in the racket surface, is becoming another index to quantify the feel. In this work, we detect friction by attaching two strain gauges close to the center of right and left frames supporting the cross strings at the middle, and aim to understand the mechanism behind friction from the viewpoint of difference in the angle of incidence of the ball when impacting the racket surface. Results suggest that there is a critical angle of incidence between 45 and 30 degrees, and that this angle is related to the feel.